Spatial heterogeneity in the photobiology of phototrophs—questions and methods - Kaňa, Radek; Eichner, Meri; Gall, Andrew; Ilioaia, Cristian (Frontiers in Photobiology, 2024)
Photosynthesis which harvests energy from the sun, whether it occurs in prokaryotes or eukaryotes, is a key biological process that untimely nourishes the biosphere. The molecular efficiencies of the photo-physical and physiological processes are intricately tied not only to the photo-physics/enzymatic kinetics of the proteins involved, but also to their spatial co-localization in membrane microdomains or in cell compartments (e.g. in membrane-less organelles). The similar heterogeneity in function can be found also between cells in isogenic cell cultures (phenotypic heterogeneity) or in filaments of phototrophic cells (e.g. heterocysts/vegetative cells in nitrogen fixing cyanobacteria). This review paper delves into the connection between the spatial (co)-localization of biomolecules (lipids, RNA, DNA, proteins, membranes compartments) and their functionality in situ. We highlight recent methodological advances in the field (e.g. super-resolution microscopy, Raman micro-spectroscopy, nanoSIMS, microsensors) and showcase applications of these methods in understanding heterogeneity on single-cell and on population-scale level. This paper thus aims to highlight the avenues that will help to unravel the molecular, cellular and ecological mechanisms in photobiology by combining up-to-date microscopy techniques with more traditional functional approaches.